Analisis Perbandingan Materi Ekspor Impor Dalam Buku IPS Kelas VI Pada Kurikulum KTSP dan Kurikulum Merdeka - Adinda Kusuma Mouristi; Sintiyani Fatikha Rizki; Firly Hernanda (GENFABET: Generasi Pendidikan Dasar, 2025)
This study investigates the comparative presentation of export and import material in sixth-grade Social Studies (IPS) textbooks under the 2006 School-Based Curriculum (KTSP) and the 2022 Independent Curriculum (Kurikulum Merdeka). The research employs a qualitative descriptive method, focusing on content analysis of two government-issued textbooks to explore differences in structure, depth, pedagogical approach, and visual representation. Findings reveal that the KTSP textbook delivers content in a compartmentalized and structured manner, emphasizing conceptual mastery through explicit maps and thematic separation of social and economic aspects. In contrast, the Independent Curriculum adopts an integrated, narrative, and project-based approach through IPAS textbooks, merging science and social studies to foster contextual understanding and critical thinking. However, the lack of concept maps and explicit economic focus in the IPAS book poses pedagogical challenges. The study concludes that curriculum design significantly influences students’ comprehension of global economic concepts and highlights the need for textbooks to align with curriculum philosophy, offer relevant examples, and support 21st-century skills. This research contributes to curriculum development discourse by emphasizing the importance of contextual and integrated textbook design in enhancing economic literacy among elementary students.